M’illumino d’immenso: L’uomo e la luce: un rapporto da studiare - Pellegrino, Giovanni (Chimica nella Scuola, 2023)
The man is lost without light. The relationship between man and light reveals many hints for teaching in terms of physics, chemistry and preventive medicine.